2010
DOI: 10.1038/nm.2174
|View full text |Cite
|
Sign up to set email alerts
|

Validated prediction of clinical outcome in sarcomas and multiple types of cancer on the basis of a gene expression signature related to genome complexity

Abstract: Sarcomas are heterogeneous and aggressive mesenchymal tumors. Histological grading has so far been the best predictor for metastasis-free survival, but it has several limitations, such as moderate reproducibility and poor prognostic value for some histological types. To improve patient grading, we performed genomic and expression profiling in a training set of 183 sarcomas and established a prognostic gene expression signature, complexity index in sarcomas (CINSARC), composed of 67 genes related to mitosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
337
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 395 publications
(354 citation statements)
references
References 38 publications
12
337
0
5
Order By: Relevance
“…13 As described previously, genomic profiles were divided into groups: a first group with few alterations mainly involving the full chromosome arm or entire chromosomal gain or loss and a second group with a high level of chromosomal complexity. The first group was called the 'complex/ arm-type' genomic profile, and the second group, the 'complex/rearranged-type' genomic profile.…”
Section: Array-cghmentioning
confidence: 99%
“…13 As described previously, genomic profiles were divided into groups: a first group with few alterations mainly involving the full chromosome arm or entire chromosomal gain or loss and a second group with a high level of chromosomal complexity. The first group was called the 'complex/ arm-type' genomic profile, and the second group, the 'complex/rearranged-type' genomic profile.…”
Section: Array-cghmentioning
confidence: 99%
“…[13][14][15] Recently, a signature associated with instability and chromosomal complexity predictive of metastatic relapse in soft tissue sarcoma was published by our team. 16 We demonstrated that this signature, based on expression profiles (CINSARC) was closely linked to the level of rearrangement of the tumoral genome in gastrointestinal stromal tumor, and created a way to identify a genomic signature combining the number and the type of tumoral genomic alterations evaluated by array-CGH. The genomic signature (genomic index) is a powerful predictor of metastatic relapse, as is the CINSARC signature.…”
mentioning
confidence: 99%
“…Une nouvelle signature moléculaire de l'évolution métastatique dans les sarcomes ayant des réarrangements chromosomiques complexes Dans l'étude que nous venons de publier [5], nous avons pu identifier une signature pronostique par une approche originale partant de mécanismes biologiques propres aux tumeurs. Ainsi cette signature, bien qu'identifiée dans les sarcomes, semble applicable à l'ensemble des cancers.…”
Section: Méthodes Classiques D'estimation Du Risque Métastatiqueunclassified
“…Dans la majorité des études, ces gènes sont identifiés en comparant les profils d'expression (niveaux d'expression de l'ensemble des gènes de la tumeur) des tumeurs ayant développé des métastases (tumeurs agressives) aux profils des tumeurs n'en ayant pas développé. Bien qu'efficace, cette approche présente l'inconvénient de produire des résultats dont la reproductibilité peut être remise en question et dont la signification biologique reste limitée [10].Une nouvelle signature moléculaire de l'évolution métastatique dans les sarcomes ayant des réarrangements chromosomiques complexes Dans l'étude que nous venons de publier [5], nous avons pu identifier une signature pronostique par une approche originale partant de mécanismes biologiques propres aux tumeurs. Ainsi cette signature, bien qu'identifiée dans les sarcomes, semble applicable à l'ensemble des cancers.…”
unclassified